Ustilago maydis Trf2 ensures genome stability by antagonizing Blm-mediated telomere recombination: Fine-tuning DNA repair factor activity at telomeres through opposing regulations. - Shahrez Syed; Sarah Aloe; Jeanette H Sutherland; William K Holloman; Neal F Lue (PLoS Genetics)
TRF2 is an essential and conserved double-strand telomere binding protein that stabilizes chromosome ends by suppressing DNA damage response and aberrant DNA repair. Herein we investigated the mechanisms and functions of the Trf2 ortholog in the basidiomycete fungus Ustilago maydis, which manifests strong resemblances to metazoans with regards to the telomere and DNA repair machinery. We showed that UmTrf2 binds to Blm in vitro and inhibits Blm-mediated unwinding of telomeric DNA substrates. Consistent with a similar inhibitory activity in vivo, over-expression of Trf2 induces telomere shortening, just like deletion of blm, which is required for efficient telomere replication. While the loss of Trf2 engenders growth arrest and multiple telomere aberrations, these defects are fully suppressed by the concurrent deletion of blm or mre11 (but not other DNA repair factors). Over-expression of Blm alone triggers aberrant telomere recombination and the accumulation of aberrant telomere structures, which are blocked by concurrent Trf2 over-expression. Together, these findings highlight the suppression of Blm as a key protective mechanism of Trf2. Notably, U. maydis harbors another double-strand telomere-binding protein (Tay1), which promotes Blm activity to ensure efficient replication. We found that deletion of tay1 partially suppresses the telomere aberration of Trf2-depleted cells. Our results thus point to opposing regulation of Blm helicase by telomere proteins as a strategy for optimizing both telomere maintenance and protection. We also show that aberrant transcription of both telomere G- and C-strand is a recurrent phenotype of telomere mutants, underscoring another potential similarity between double strand breaks and de-protected telomeres.